Decolonizing Education from a Nurturing Approach - Sylvia Contreras Salinas; Mónica Ramírez Pavelic (Universidad Nacional, Costa Rica, 2014)
This paper seeks to problematize some changes currently imposed on education, as part of the discussions on the deconstruction of colonized education versus a type of education denominated nurturing. From the perspective of the dialogue of knowledge and interculturality, the term nurturing highlights the mutual care and creation between human beings and uses a type of education that is developed in multiple spaces, as an expansion of knowledge conceived in the daily, social, historical and personal experience of the communities. From this premise, this paper has been woven using the threads of discourse, highlighting the words of Juan, a farmer in central Chile, since, from a Foucauldian proposition, strength and meaning of discourse are given by the positions of power; therefore, the authors take the challenge of putting into circulation the thought of a man immersed in the everyday world of the biotics.